THE ROLE OF EDUCATION IN HABITUATION OF VALUES IN THE ORAL TRADITION OF PNO ADAT IN GROWING THE CHARACTER OF ANTI-CORRUPTION CULTURE IN THE MILLENNIAL GENERATION IN KERINCI - Deri Saputra; Futri Zakiyah Apria Sapawer (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
This paper focuses on disclosing the values ​​in traditional expressions of Pno Adat to the Kerinci people as an effort to inculcate an anti-corruption culture in the millennial generation in Kerinci Regency. Corruption cases are carried out by individuals from various backgrounds, ranging from high-ranking state officials to village officials. Eradicating corruption means fighting and preventing corruption. Enforcement is carried out by a state institution called the Corruption Eradication Commission (KPK), while the prevention of corruption can be carried out by the community, one of which is by cultivating character through cultural values ​​in both formal and non-formal education. in society. Kerinci Regency has an oral tradition of Pno Adat which has value in character building. This customary principle is upheld by the Kerinci people as a character value related to anti-corruption cultural integrity. Data and information were obtained from field observations and interviews with key informants, namely the Karang Setio customary stakeholders. In addition, researchers conducted journal literature related to the research theme. It is hoped that the results of the research can become a reference and guideline for the community, especially the millennial generation in the Kerinci community that there is no corrupt Kerinci culture where there are character values ​​in the anti-corruption culture contained in it such as Compliance, Responsibility, Complete Work, Fairness, and Integrity. The value of Pno Adat which has been upheld by the community and implemented by the people of Kerinci. Therefore, these values ​​must be inherited and passed on to the younger generation as the successors of the Kerinci nation and culture.